2008
DOI: 10.1111/j.1532-849x.2008.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Comparison of Vertical Marginal Gaps of CAD/CAM Titanium and Conventional Cast Restorations

Abstract: There was no difference between the vertical marginal gaps of the CAD/CAM and WAX/CAM. The WAX/CAST technique resulted in smaller vertical marginal gaps than either CAD/CAM or WAX/CAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 12 publications
3
76
2
4
Order By: Relevance
“…Several studies reported a larger marginal or internal gap for CAD/CAM-fabricated restorations than for conventionally made restorations. 9,16 In contrast, other studies showed that CAD/CAM fabricated restorations also had a clinically acceptable marginal fit compared with conventionally made restorations. 17 There are several scan methods to obtain digital data from the prepared tooth for fabrication of ceramic restorations, especially zirconia prostheses.…”
Section: 대한치과보철학회지 55권 2호 2017년 4월 최현석•조진현 서로 다른 두 가지 스캔법을 이용하여 제작된 mentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies reported a larger marginal or internal gap for CAD/CAM-fabricated restorations than for conventionally made restorations. 9,16 In contrast, other studies showed that CAD/CAM fabricated restorations also had a clinically acceptable marginal fit compared with conventionally made restorations. 17 There are several scan methods to obtain digital data from the prepared tooth for fabrication of ceramic restorations, especially zirconia prostheses.…”
Section: 대한치과보철학회지 55권 2호 2017년 4월 최현석•조진현 서로 다른 두 가지 스캔법을 이용하여 제작된 mentioning
confidence: 95%
“…8 In this regard, many authors have compared the marginal or internal fit of CAD/CAM-fabricated restorations with those of conventionally made restorations. 9,[16][17][18][19][20][21][22] However, the results of such studies vary widely because of differences in sample size, measurements per specimen, measurement method, cement space, and the CAD/CAM systems used. Several studies reported a larger marginal or internal gap for CAD/CAM-fabricated restorations than for conventionally made restorations.…”
Section: 대한치과보철학회지 55권 2호 2017년 4월 최현석•조진현 서로 다른 두 가지 스캔법을 이용하여 제작된 mentioning
confidence: 99%
“…There is no consensus in literature on the limits of clinically acceptable marginal adaptation, some support a value lower or equal to 120 µm, [14][15] others concluded that it should be lower than 100 µm [16][17][18] and there are still those who argue for a maladjustment lower than 75 µm 19 or between 20-45 µm, 20 however, these last ones are rarely found in clinic. The marginal adaptation promoted by the CAD/CAM system has been comprehensively studied and compared regarding different clinical situation and through different methodologies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…우선 재료의 불필요한 소모성이 발생하고, 지속 적인 CAM 장비의 사용에 따른 유지비용이 높으며, 생산과 정 및 곡면 가공 등의 공정에서 시간적 손실이 크다는 점이 지적되고 있다 [2][3][4] . 또한 이러한 가공 방식을 적용한 경우 금 속 코핑의 가장 중요한 평가 요소인 변연 및 내면 적합도가 우수하지 못하다는 연구결과들이 있다 5,6) .…”
Section: 서 론unclassified